Development of normative neuropsychological performance in Thailand for the assessment of HIV-associated neurocognitive disorders - Heaps, Jodi; Valcour, Victor; Chalermchai, Thep; Paul, Robert; Rattanamanee, Somprartthana; Siangphoe, Umaporn; Sithinamsuwan, Pasiri; Chairangsaris, Parnsiri; Nidhinandana, Samart; Tipsuk, Somporn; Suttichom, Duanghathai; Fletcher, James; et al. (Journal of clinical and experimental neuropsychology, 2013)
International studies of HIV-associated neurocognitive disorder (HAND) are needed to determine the viral and host factors associated with cognitive impairment particularly as more than 80% of HIV+ subjects reside in resource-limited settings. Recent diagnostic nomenclature of HAND requires comparison of cognitive performance specifically to local normative data. To evaluate this need for local norms, we compared normative data obtained locally in Thailand to Western norms. The current study examined cognitive performance in 477 seronegative Thai participants (male = 211, female = 266) who completed a battery of tests sensitive to cognitive changes in HIV. The cohort was divided into three age brackets (20-34; 35-49; 50-65 years) and four educational levels (no education or primary education, less than secondary certificate, high-school/associates degree, bachelor's degree or greater). The Thai cohort was compared (using analysis of covariance, ANCOVA) on a number of measures to a seronegative US cohort (n = 236; male = 198, female = 38) to examine cultural differences in performance. Normative data are provided with age and education stratification. The Thai and US groups performed significantly differently on all neuropsychological measures with the exception of verbal fluency. The Thai group performed better on measures of verbal learning (p < .001) and memory (p < .001) and measures of psychomotor speed (p < .001). Education was a more powerful predictor of performance in the Thai cohort than in the US group. These results highlight the continued need for the development of normative data within local populations. The use of Western norms as a comparison group could lead to inaccurate identification of HAND in culturally distinct groups.